The health impacts of a community biogas facility in an informal Urban settlement: does training matter?. Issue 2 (3rd April 2019) - Moncada, Stefano; Bambrick, Hilary; Briguglio, Marie
ABSTRACT: Community biogas facilities are being implemented in many informal urban settlements across Africa, often funded by foreign aid. We measured the public health impacts of a facility in Ethiopia, particularly the effects of training, in the context of extreme poverty. Two waves of panel-data were generated by household surveys (N = 200 per wave), informed by participatory focus groups, and a propensity-score matching technique was applied. After controlling for household distance from the facility, training itself generated positive effects on health including use of improved sanitation facilities and self-assessed health. We conclude that training should be considered a key component in biogas development.